Information-theoretic estimation of preference parameters: Macroeconomic applications and simulation evidence - Allan W. Gregory; Jean-Francois Lamarche; Gregor W. Smith (Queen's University, Department of Economics, 2001)
This paper investigates the behaviour of estimators based on the Kullback-Leibler information criterion (KLIC), as an alternative to the generalized method of moments (GMM). We first study the estimators in a Monte Carlo simulation model of consumption growth with power utility. Then we compare KLIC and GMM estimators in macroeconomic applications, in which preference parameters are estimated with aggregate data. KLIC probability measures serve as useful diagnostics. In dependent data, tests of overidentifying restrictions in the KLIC framework have size properties comparable to those of the J-test in iterated GMM, but superior size-adjusted power.
Keywords: C13; C14; E21; 330; KLIC estimation; generalized method of moments; Monte Carlo